A directional distance function approach to void the non-Archimedean in DEA*. Issue 5 (4th May 2018) - Färe, Rolf; Charles, Vincent
Abstract: Over the past years, the data envelopment analysis (DEA) methodology has registered widespread use among researchers from many fields. Furthermore, it is important to note that the non-Archimedean infinitesimal, ɛ, is a key concept in DEA models. Nevertheless, it is known that some computational difficulties arise when using ɛ in DEA. In this short communication, we show how the non-Archimedean may be voided using a directional distance function approach. Thus, our approach avoids choosing a real number (10 −5 or 10 −6 ) as a value for ɛ or estimating the same.